Zintai-Cintai (o gal Žintai?) bei Prūzai-Prūsai (o gal Prūžai?) - Palmaitis, Letas (Baltistica, 2010)
ZINTAI-CINTAI (why not ŽINTAI?) and PRŪZAI-PRŪCAI (why not PRŪŽAI?)The historically attested spellings of the Natangian village Zinten – 1419 Sinthen, 1476 Szynthen, 1508 Zcingten (Gerullis APON) – show a graphic variation of the letters s, sz, zc before vowels. This was a typical means of avoiding a voiced pronunciation of s in this position in medieval Latin manuscripts written by Germans (cf. the spellings Pruzi, Pruzzi for Prussians, Pruciam for Prussia, Ruzzia, Rusciae for Russia). Therefore the correct Old Prussian reconstruction of the name of the village should be *Sintai corresponding to the Lithuanian proper names Sintautai, Sintautas.An etymology seems to be possible on the basis of a comparison with the Lithuanian verbs sintė́ti, siñti.Current reconstructions like Zintai, Žintai should be rejected, let alone the comparison with OPr. sindats, which is based on pure consonance.
Keywords: prūsų kalba; rašyba; ortografija; fonetika; vietovardžiai; Zintai; Zinten